Human leukocyte antigen-G expression and polymorphisms promote cancer development and guide cancer diagnosis/treatment - Zhang, Yanwen (Oncol Lett, 2018)
Human leukocyte antigen-G (HLA-G) is a non-classical HLA molecule, predominantly expressed in cytotrophoblast cells to protect the fetus during pregnancy. Notably, a high frequency of HLA-G expression has been observed in a wide variety of cancer types in previous studies. Furthermore, HLA-G expression in cancer has been considered to be detrimental, since it can protect cancer cells from natural killer cell cytotoxic T lymphocyte-mediated destruction, promote tumor spreading and shorten the survival time of patients by facilitating tumor immune evasion. In addition, HLA-G polymorphisms have been investigated in numerous types of cancer and are considered as risk factors and predictive markers of cancer. This review focuses on HLA-G expression and its polymorphisms in cancer, analyzing the mechanisms of HLA-G in promoting cancer development, and evaluating the potential and value of its clinical application as a diagnostic and prognostic biomarker, or even as a prospective therapeutic target in certain types of tumors.